2005
DOI: 10.1097/01.mao.0000185050.69394.48
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Dexamethasone and Hyaluronic Acid in Patients with Low-Frequency and Ménière's-Associated Sudden Sensorineural Hearing Loss

Abstract: Intratympanic combined dexamethasone/hyaluronic acid application provides a reliable and safe therapeutic option for improvement of hearing in patients with isolated low-frequency idiopathic sudden sensorineural hearing loss or sensorineural hearing loss resulting from Ménière's disease who have failed intravenous steroid and vasoactive treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 17 publications
0
39
0
3
Order By: Relevance
“…This result is similar to our previous study [9] and Ahn et al's [18] study which showed that early salvage ITDI may provide more rapid hearing improvement than late salvage ITDI, especially at low frequency. In fact, it was reported that intratympanic combined dexamethasone/ hyaluronic acid injection showed hearing improvement in patients with isolated low-frequency idiopathic SSNHL or sensorineural hearing loss from Meniere's disease who have failed intravenous steroid and vasoactive treatments [19]. This phenomenon may be explained by the differential vulnerability of cochlear turns in the sense that apical hair cells are more resistant to toxic stimuli including ototoxic drugs or noise than basal hair cells [20,21].…”
Section: Discussionmentioning
confidence: 92%
“…This result is similar to our previous study [9] and Ahn et al's [18] study which showed that early salvage ITDI may provide more rapid hearing improvement than late salvage ITDI, especially at low frequency. In fact, it was reported that intratympanic combined dexamethasone/ hyaluronic acid injection showed hearing improvement in patients with isolated low-frequency idiopathic SSNHL or sensorineural hearing loss from Meniere's disease who have failed intravenous steroid and vasoactive treatments [19]. This phenomenon may be explained by the differential vulnerability of cochlear turns in the sense that apical hair cells are more resistant to toxic stimuli including ototoxic drugs or noise than basal hair cells [20,21].…”
Section: Discussionmentioning
confidence: 92%
“…In a guinea pig model, 1 h after IT treatment, perilymph levels of dexamethasone were 20% higher when used in the presence of HA (9.5 mg/ml) compared with dexamethasone alone [Chan-drasekhar et al, 2000]. Although these results were not statistically significant, follow-up human clinical trials using IT dexamethasone combined with HA (0.2 mg/ml) reported significant improvement in hearing in specific subgroups of patients with ISSHL or Ménière's disease Selivanova et al, 2005]. However, these were not controlled trials, making it unclear whether HA played a role in these results.…”
mentioning
confidence: 87%
“…These include repeated transtympanic injections [Chandrasekhar et al, 2000;Chandrasekhar, 2001;Ho et al, 2004;Gouveris et al, 2005;Selivanova et al, 2005], instillation through ventilation tubes [Parnes et al, 1999;Parnes, 2004, 2005], and continuous infusion (up to 28 days) through microcatheters temporarily implanted in the round window niche [Kopke et al, 2001;Plontke et al, , 2009Salt and Plontke, 2005].…”
mentioning
confidence: 99%
“…A very rapid chemical conversion within the cochlea from drug salt to active drug occurs within 15 min [Hargunani et al, 2006] and dexamethasone is completely removed from the inner ear in under 24 h [Parnes et al, 1999;Chandrasekhar et al, 2000;Liu et al, 2004;Hargunani et al, 2006]. Third, transtympanic delivery of steroids is already in otologic practice [Gianoli and Li, 2001;Ho et al, 2004;Gouveris et al, 2005;Selivanova et al, 2005]. Fourth, the round window is accessible during cochlear implant surgery.…”
Section: Introductionmentioning
confidence: 99%